2018
DOI: 10.1158/1541-7786.mcr-17-0547
|View full text |Cite
|
Sign up to set email alerts
|

The Long (lncRNA) and Short (miRNA) of It: TGFβ-Mediated Control of RNA-Binding Proteins and Noncoding RNAs

Abstract: RNA-binding proteins (RBP) and noncoding RNAs (ncRNA), such as long noncoding RNAs (lncRNA) and microRNAs (miRNA), control co- and posttranscriptional gene regulation (PTR). At the PTR level, RBPs and ncRNAs contribute to pre-mRNA processing, mRNA maturation, transport, localization, turnover, and translation. Deregulation of RBPs and ncRNAs promotes the onset of cancer progression and metastasis. Both RBPs and ncRNAs are altered by signaling cascades to cooperate or compete with each other to bind their nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 76 publications
1
53
0
Order By: Relevance
“… 276 , 277 LncRNAs, and other noncoding RNAs such as miRNAs, work in conjunction with RNA-binding proteins (RBPs), to alter both co- and post-transcriptional gene regulation. 278 There are many cases in which, through epigenetic modifications, lncRNAs act as gene suppressors though lncRNAs may also act as gene activators. 279 , 280 MANCR (mitotically-associated noncoding RNA) is a lncRNA of particular interest, especially in its proposed association to TNBC, in the current search for therapeutic targets for its noted upregulation in breast cancer cells.…”
Section: Epigenetics and Non-coding Rnas In Breast Cancermentioning
confidence: 99%
“… 276 , 277 LncRNAs, and other noncoding RNAs such as miRNAs, work in conjunction with RNA-binding proteins (RBPs), to alter both co- and post-transcriptional gene regulation. 278 There are many cases in which, through epigenetic modifications, lncRNAs act as gene suppressors though lncRNAs may also act as gene activators. 279 , 280 MANCR (mitotically-associated noncoding RNA) is a lncRNA of particular interest, especially in its proposed association to TNBC, in the current search for therapeutic targets for its noted upregulation in breast cancer cells.…”
Section: Epigenetics and Non-coding Rnas In Breast Cancermentioning
confidence: 99%
“…TGF-β signaling is regulated by miRNAs. Mechanistically, there are three types of interactions between TGF-β signaling and microRNAs: i) TGF-β regulates expressions of miRNAs, ii) miRNAs regulate the expression of genes involved in TGF-β signaling (Figure 2), and iii) miRNAs interfere with the TGF-β-induced process, such as EMT [269][270][271][272][273]. In the following chapters, we discuss the importance of these complex networks of interactions that contribute to the development and progression of genitourinary cancers, as well as responses to therapy.…”
Section: Micrornas and Tgf-β Signaling In Gcmentioning
confidence: 99%
“…TGF-β signaling has many regulatory roles in development, with alterations in this signaling pathway having been associated with the pathogenesis of various diseases, including fibrotic disease, cardiovascular disease and cancer [ 14 , 15 , 16 , 17 ]. Previous studies have shown that the TGF-β signaling pathway embraces the miRNA pathway as an important component of its downstream signaling cascades [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In the present review, I summarize the connection between TGF-β signaling and miRNAs with a particular focus on: (1) regulation of miRNA expression by TGF-β signaling; (2) modulation of TGF-β signaling by miRNAs; (3) miRNA-mediated regulation of cell state transitions, such as epithelial–mesenchymal transition (EMT) and endothelial–mesenchymal transition (EndMT); and (4) crosstalk between miRNA and TGF-β pathways in cancer.…”
Section: Introductionmentioning
confidence: 99%